PROBLEMATIKA PENGELOLAAN JALAN DI ERA OTONOMI DAERAH: KEWENANGAN VERSUS KEMAMPUAN - Yana Sahyana (Jurnal Ilmiah Wahana Bhakti Praja, 2022)
Road management in the era of local autonomy is considered still face problems in terms of regulation which negatively impacts to its implementation. The regulation of the authority to administer local governments with the broadest principle of autonomy has apparently been narrowed at the level of its implementation in line with changes in relevant laws. As a consequence, the regional authority, which was originally very broad, has changed to become narrow again, so that certain functions are not optimal. One indication is the reversalof road management from the province, district or city to the central government, so this has become an anomaly in the current era of localautonomy. This paper will try to discuss three important issues relating to road management from a legal perspective. First, the arrangement of the division of authority in the management of roads between government level in legislation. Second, the implementation of road management by the central, provincial, district and city governmentsin the era of local autonomy. Third, efforts to optimize the function of roads as a means of regional development and promotion in the era of local autonomy.